2016
DOI: 10.14260/jemds/2016/333
|View full text |Cite
|
Sign up to set email alerts
|

Application of Amit Jain’s Scoring System in Diabetic Foot Amputees

Abstract: BACKGROUNDMajor amputation is an unfortunate outcome of diabetic foot complications. There was no way to assess the justification of major amputation or the risk associated for the major amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A surgeon often gets to deal with operative complications like abscess, wet gangrene, necrotizing fasciitis etc and they often need hospitalization. Studies from India also have shown that the major amputation most commonly is seen in type 1 diabetic foot complications [18,19] . In Kalaivani et al series [19] , 85.7% of all major amputation has type 1 diabetic foot complication.…”
Section: Amit Jain's Classification For Diabetic Footmentioning
confidence: 99%
See 1 more Smart Citation
“…A surgeon often gets to deal with operative complications like abscess, wet gangrene, necrotizing fasciitis etc and they often need hospitalization. Studies from India also have shown that the major amputation most commonly is seen in type 1 diabetic foot complications [18,19] . In Kalaivani et al series [19] , 85.7% of all major amputation has type 1 diabetic foot complication.…”
Section: Amit Jain's Classification For Diabetic Footmentioning
confidence: 99%
“…Studies from India also have shown that the major amputation most commonly is seen in type 1 diabetic foot complications [18,19] . In Kalaivani et al series [19] , 85.7% of all major amputation has type 1 diabetic foot complication. Even in recent series of Jain et al [2] , it was seen that most major amputation were performed in patients with type 1 diabetic foot complications.…”
Section: Amit Jain's Classification For Diabetic Footmentioning
confidence: 99%